Training of Medical Rescue teams in Ghana - Zieliński, Ewa; Sas, Katarzyna; Zukow, Walery (Journal of Education, Health and Sport, 2018)
During the numerous trips to African countries and during the implementation of education and prevention programs in Ghana, the problem of lack of knowledge and skills in providing premedical help and handling of medical equipment among Medical Emergency Teams was noticed.The Paramedics for Africa project was created. It was realized in 2017 in the capital of Ghana in Accra and the city of Dormaa. One of the goals of the project was medical training and equipment retrofitting of emergency ambulance teams. 81 paramedics were trained.The work describes own experience from the implementation of an educational project.